Pengaruh Pendekatan Konflik Kognitif Terhadap Pemahaman Konsep Pada Materi Gerak Lurus - Sutrio Sutrio; Muhammad Makhrus; Armi Larasati (Universitas Islam Negeri Maulana Malik Ibrahim Malang)
This study aims to determine the effect of the cognitive conflict approach on the conceptual understanding of senior high school students in class X on straight motion material. This type of research is a pre-experimental research design with One Group Pretest-Posttest Design. The population in this study were all students of class X MIPA State Senior High School 1 Narmada. The research sample was obtained using a positive sampling technique, obtained class X MIPA 1 as experimental class 1, class X MIPA 2 as experimental class 2, and class X MIPA 3 as experimental class 3. Data collection on conceptual understanding used multiple-choice tests of 15 questions. Hypothesis test analysis used a statistical paired sample t-test and showed that Ho was rejected and Ha was accepted. This shows that the cognitive conflict approach affects students' conceptual understanding of straight motion material.